Numerical simulation and experimental verification of the airfoil electrothermal deicing system performance. (3rd October 2021) - Zhu, Cheng-Xiang; Wang, Yuan; Zhao, Ning; Zhu, Chun-Ling; Liu, Chong-Yang
ABSTRACT: Electrothermal deicing system is one of the most promising aircraft icing protection systems. This paper has used a numerical simulation method to study the airfoil electrothermal deicing system. The multilayer structure heat transfer model of the electrothermal deicing system was established. Enthalpy method was introduced to simulate the ice-water-phase transition process. AUX method was used to discretize the heat conduction equation, and a method for numerical calculation of two-dimensional airfoil electrothermal deicing system performance was developed. We designed and produced an airfoil test model with the electrothermal deicing system. Electrothermal deicing test in the large-scale icing wind tunnel was carried out, which verified the correctness of the proposed numerical simulation method. We analyzed the effect of heating control parameters on the performance of the electrothermal deicing system. Findings of this study are considered instrumental in the design of high-efficiency aircraft electrothermal deicing systems.